2021
DOI: 10.1002/ueg2.12114
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's esophagus surveillance in a prospective Dutch multi‐center community‐based cohort of 985 patients demonstrates low risk of neoplastic progression

Abstract: Background and Aims: Barrett's esophagus (BE) is accompanied by an increased risk of developing esophageal cancer. Accurate risk-stratification is warranted to improve endoscopic surveillance. Most data available on risk factors is derived from tertiary care centers or from cohorts with limited surveillance time or surveillance quality. The aim of this study was to assess endoscopic and clinical risk factors for progression to high-grade dysplasia (HGD) or esophageal adenocarcinoma (EAC) in a large prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Two prior studies demonstrated that LGD diagnosed by a community pathologist, was downgraded to NDBE in 73 %–85 % after review by a BE expert pathologist. After downstaging to NDBE, the risk of progression to HGD/EAC was < 1 % per patient-year 4 5 . In contrast, for confirmed LGD, the risk of malignant progression increased to 9 %–13 % per patient-year 6 7 .…”
Section: Introductionmentioning
confidence: 98%
“…Two prior studies demonstrated that LGD diagnosed by a community pathologist, was downgraded to NDBE in 73 %–85 % after review by a BE expert pathologist. After downstaging to NDBE, the risk of progression to HGD/EAC was < 1 % per patient-year 4 5 . In contrast, for confirmed LGD, the risk of malignant progression increased to 9 %–13 % per patient-year 6 7 .…”
Section: Introductionmentioning
confidence: 98%
“…Increasing age has been showed to be associated with an increased risk of progression in a recent meta-analysis; however, this association did not remain statistically significant in a more restricted analysis including only studies that reported multivariate analysis adjusted for age, sex, dysplasia, and BE length [3]. Additionally, the value of age is a questionable risk factor, since the low progression rate of 0.12–0.78% per patient-year needs to be weighted carefully against the invasiveness and costs of endoscopic surveillance in elderly and frail BE patients [4, 5].…”
Section: State Of the Art And Todays Mistakesmentioning
confidence: 99%
“…LGD and p53 Immunohistochemistry Whereas patients with nondysplastic (ND) BE carry a very low risk for progression (0.12-0.78%/year), the progression rate increases substantially in the presence of a histologic diagnosis of LGD [4,5]. However, the diagnosis of LGD is challenging due to several reasons.…”
Section: State Of the Art And Todays Mistakesmentioning
confidence: 99%
“…These biopsy protocols essentially reflect the subtlety of a relevant proportion of the lesions 3 . Limited adherence to ‘blind chase’‐biopsy protocols and varying dysplasia detection rates, 3 the relevance of (verified) low‐grade dysplasia, 4 and debates around the efficiency of current surveillance protocols 2,3 have sparked efforts towards improved risk‐stratification protocols 2,5 and ‘optical biopsy’ to reduce the biopsy‐load in BE surveillance and improve its quality.…”
mentioning
confidence: 99%
“…Barrett's oesophagus (BE) confronts endoscopists with labour‐intensive surveillance protocols 1 in the context of relatively low‐prevalence cohorts 2 . These biopsy protocols essentially reflect the subtlety of a relevant proportion of the lesions 3 .…”
mentioning
confidence: 99%